Cepharanthine hydrochloride inhibits prostate cancer progression by modulating gut microbiota and metabolites - Hui Li; Xing Luo; Peng He; Peng He; Zongming Dong; Yongming Jia; Bishao Sun; Ji Zheng; Jingzhen Zhu (Frontiers in Pharmacology)
BackgroundCepharanthine Hydrochloride (CH) is widely used in clinical settings to alleviate leukopenia caused by various tumors following radiotherapy and chemotherapy. However, it remains unclear whether CH have an inhibitory effect on the progression of prostate cancer, and whether this effect is mediated by gut microbiota. To address this question, the present study constructed normal mouse models of prostate cancer, as well as antibiotic-treated mouse models of prostate cancer.MethodsCH were then administered via gavage to both groups of model mice. After treatment, the tumor sizes of the mice were measured, and feces, blood, and tumor tissues from both groups were collected for 16S rDNA, metabolomics, and transcriptomics sequencing analysis.ResultsResults showed CH treatment significantly suppressed prostate cancer growth in mice without antibiotic cocktail pretreatment, but not in antibiotic-pretreated mice. 16S rRNA sequencing revealed distinct gut microbiota alterations in CH-Ctrl versus Ctrl/CH-ABX groups, with increased g_Blautia, g_Lactobacillus, g_Butyricicoccus and decreased g_Akkermansia abundances. Metabolomic analysis identified 240 and 123 differentially abundant metabolites in CH-Ctrl vs Ctrl and CH-ABX, respectively. RNA-seq detected 579 and 530 differentially expressed genes in CH-Ctrl vs Ctrl and CH-ABX, respectively. Correlation analysis of differential gut microbiota, metabolites, and genes suggested that CH might inhibit prostate cancer growth by increasing the relative abundance of g_Blautia, g_Lactobacillus, and g_Butyricicoccus, suppressing g_Akkermansia proliferation, enhancing Acetylglycine metabolite production, upregulating Ttpa, Gm14964, Shc3, Elovl4 gene expression, and downregulating Gm10531, Bc021767 gene expression.ConclusionThis study is the first to explore the potential mechanisms of gut microbiota-mediated CH treatment for prostate cancer, providing a scientific basis for the application of CH in PCa therapy.